Production Efficiency of Cost of Goods Sold at PT. Malang Raya Express through the Order Costing Method - Siti Rosyafah; Ummi Sa'adah; Dhuihitta Mahardhika Lakshita (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2023)
Current global crisis and intense competition among businesses have led to vigilant in financial management strategies. This research aims to investigate the impact of job order costing on the optimization of production expenditure efficiency. The study uses a qualitative data approach to analyze the production cost associated with the KWH Meter job. The findings reveal that job order costing is more cost-effective compared to the full costing. The analytical methodologies in this inquiry included identifying overhead costs, organizing production cost allocation, scrutinizing factory overhead cost calculations, and efficiency evaluation. The study concludes that job order costing is a more efficient approach to determine production cost. This research can help businesses improve their financial management strategies and optimize production expenditure efficiency.